2008
DOI: 10.1002/mrc.2204
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the NMR spectra of nucleotides by DFT calculations: cyclic uridine monophosphate

Abstract: We present an experimental and quantum chemical NMR study of the mononucleotide cyclic uridine monophosphate in water. Spectral parameters ((1)H and (13)C chemical shifts and (1)H--(1)H, (13)C--(1)H, (31)P--(13)C and (31)P--(1)H spin-spin coupling constants) have been carefully obtained experimentally and calculated using DFT methods including the solvent effect and the conformational flexibility of the solute. This study confirms that the (1)H and (13)C spectra of polar, flexible molecules in aqueous solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 40 publications
2
72
0
2
Order By: Relevance
“…The contributions from these factors have been discussed in many works devoted to QM chemical shift prediction. [20,23,50,51] Figs 9 and 10 show plots of the HOSE-and QM-calculated 13 C chemical shifts versus experimental shifts for all atoms included in the structures presented in Table 2S, 274 shifts in total.…”
Section: Statistical Comparison Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contributions from these factors have been discussed in many works devoted to QM chemical shift prediction. [20,23,50,51] Figs 9 and 10 show plots of the HOSE-and QM-calculated 13 C chemical shifts versus experimental shifts for all atoms included in the structures presented in Table 2S, 274 shifts in total.…”
Section: Statistical Comparison Of Methodsmentioning
confidence: 99%
“…Stereoisomer 5 was ranked as the most likely isomer with MAE(HOSE) = 2.93 ppm and MAE(NN) = 3.89 ppm while the MAE(QM) value found for structure 5 using the GIAO approach was 5.3 ppm. [30] In a separate study, [51] Bagno et al carried out QM 13 C chemical shift calculations for structure 6. The MAE(QM) value = 6.83 ppm and the authors concluded that the QM approach allows 13 C NMR prediction for a polar, flexible molecule in aqueous solution with a high level of accuracy, comparable to that obtained for less complex systems.…”
Section: Statistical Comparison Of Methodsmentioning
confidence: 99%
“…First, we consider the 11 The relationship between the theoretical and experimental chemical shifts can be seen easily from the linear fitting of the theoretical dataset to the experimental one. [19,29,33,35] The linear regression equations for the four sets of calculated chemical shifts can be expressed as…”
Section: Chemical Shieldings/shifts Of Species Other Than (Cf 3 ) 3 Bcomentioning
confidence: 99%
“…[2][3][4][5][6] Characterization of the structural arrangements of such polar organometallics in solution is now generally performed by using NMR spectroscopy, which affords convenient access to important physiA C H T U N G T R E N N U N G cochemical characteristics. [7][8][9] In particular, the 1 J Li,C coupling constant is a useful parameter which can be directly related to the degree of aggregation of the organolithium compound, independent of the nature of the organic chain. Indeed Bauer, Winchester, and Schleyer have proposed an empirical formula [BWS rule; Eq.…”
Section: Introductionmentioning
confidence: 99%